ADHD symptoms and psychosocial challenges: a North-West University case study - Mpho Mpetha; Curwyn Mapaling; Frans Koketso Matlakala; Herman Grobler (Frontiers in Education)
IntroductionAttention Deficit Hyperactivity Disorder (ADHD), a neurodevelopmental psychological disorder characterised by inattention, hyperactivity, and impulsivity, poses significant challenges to individuals, especially within higher education contexts. The psychosocial impacts of ADHD symptoms on university students remain inadequately understood.MethodsThis exploratory qualitative case study aimed to investigate the psychosocial challenges faced by students with ADHD symptoms at North-West University (NWU). A purposive sample of 12 participants was recruited through digital advertisements posted on NWU’s student Facebook pages. Data were collected via online semi-structured interviews and analysed using thematic analysis.ResultsFindings revealed that students experienced significant anxiety, depression, feelings of isolation and withdrawal, and difficulties with the extended duration of lectures. These psychosocial challenges notably affected their overall academic experience and well-being.DiscussionThe study emphasises the urgent need for policy amendments and practical adaptations at higher education institutions like NWU. Recommendations include restructuring lecture schedules to incorporate shorter durations and regular breaks, and enhancing university resources dedicated to supporting students with ADHD symptoms. Limitations of this study include a small sample size, its cross-sectional nature, and reliance on self-reported data. Future research should address these limitations to provide deeper insights into the experiences of university students with ADHD symptoms.